(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Sanitation is one of the basic determinants of quality of life and human development index. Poor sanitation and hygiene practices are major causes of ill health and socio-economic problems, and portray a major development barrier in most developing countries. Meru County government loses 816 million shillings each year due to poor sanitation, with pit latrine coverage of 60%. Diarrhea and related illnesses account for 16% of deaths among the children below 5 years and stand second to pneumonia in Meru County. This study sought to assess the motivational determinants influencing sanitation practices in rural settlements of Tigania East Sub- County, in Meru County. A descriptive study design was used with a sample size of 150 households calculated using Fisher’s formula. Cluster sampling technique was used in categorizing Tigania East Sub-County into its respective wards and simple random sampling technique employed in selection of households from the clusters. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 25 using descriptive and inferential statistics for quantitative, while qualitative data was presented thematically. Findings revealed that 70% of the respondents were not satisfied with using sanitation facilities in poor states. Absence of safety, privacy, poor design of the superstructure, inaccessibility of toilets, and cultural beliefs encouraged poor sanitation practices such as open defecation. Some of the residents believed that children faeces are safe and was disposed in the garden, bush and composite pit. This was influenced by behaviour of the people within the community due to lack of knowledge on effects on sanitation practices. The study recommends the need to address motivational determinants as they influence sanitation practices in rural areas through training to the residents. The study also recommends government collaboration with sanitation-related bodies coupled with health promotion activities by Public Health Officers to support the construction of improved toilets in the study area